Challenging modernity: The Luntas, modern ludruk and young audiences’ acceptance - Firtha Ayu Rachmasari; Delmarrich Bilga Ayu Permatasari (Universitas Trunojoyo Madura, 2020)
The Luntas, a modern ludruk group from Surabaya, is bringing back ludruk with a new style. This is an effort and strategy to attract urban communities, especially young people. This study aims to determine whether the strategies and efforts of The Luntas are successful. The researcher explores the audience’s acceptance by using Stuart Hall’s theory of how the message is conveyed (encoding) and the attitude of receiving the message (decoding). The data was collected through in-depth interviews with the founders of The Luntas as the encoder and the audience as the decoder. The process of selecting audiences as informants must meet several criteria: the informant is the audience for the show “Arti Sebuah JAS” performance; age between 15 to 30 years old; has watched The Luntas live performance more aged between 15 and 30 years; have watched The Luntas live performance more than once; have watched other ludruk shows besides The Luntas at least once. Based on these criteria, the researcher found nine informants. The study results found that five informants in accordance with the dominant-hegemonic category agreed with and accepted The Luntas strategy. Meanwhile, four other informants understood the strategy but tended to negotiate.